Pelaksanaan Kewenangan Pemerintah Daerah Dalam Upaya Rehabilitasi Pasca Bencana Gempa Bumi Di Nagari Kajai Pasaman Barat - Zuhdi, Aprizon; Yuslim, Yuslim; Khairani, Khairani (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Natural disasters seem to be daily events and news in Indonesia, and even the world. Various forms of disasters have caused enormous losses, both moral and material losses. The earthquake that occurred on February 25 2022, centered in Talamau District, West Pasaman Regency, was a major disaster. As the epicenter of the earthquake, Talamau District was the worst affected area. It was recorded that 25 people were killed and 465 people were injured, 14 of whom were residents of East Pasaman. Apart from immaterial losses, the earthquake that occurred in West Pasaman Regency also resulted in material losses such as heavily damaged public facilities, schools and houses of worship (mosques). Due to this disaster, thousands of West Pasaman residents are waiting for development assistance from the government, however the expected assistance is still being delayed before it can be realized immediately by the Regional Government. This problem needs to be formulated into two problem statements. First, how is the implementation of regional government authority in post-earthquake rehabilitation efforts in Nagari Kajai, West Pasaman Regency? Second, what are the obstacles to implementing Regional Government Authority in post-earthquake rehabilitation efforts in Nagari Kajai, West Pasaman Regency? This research is a type of normative legal research or doctrinal legal research. The results of this research show that as a form of disaster management, the West Pasaman Regional Government carries out rehabilitation activities, one of these activities is providing assistance to repair houses for people affected by the disaster. This development is carried out through three systems, namely: independent reinbuce, facilitator reinbuce, and self-sufficiency. In an effort to exercise its authority to carry out post-disaster rehabilitation, the Regional Government encountered obstacles, including APIP's finding that there was an error in collecting data on houses of disaster victims which required data collection again, which took quite a long time and the regional financial capacity was inadequate.